INDONESIA'S MANPOWER BEHAVIOR IN MANAGING FUNDS FOR SUSTAINABILITY - Denik Wahyu Nilasari; Agus Sukoco; Arasy Alimudin; David Martin (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this study was to generate a model of the use of foreign funds obtained by foreign workers, in r numbers improve the living standard and sustainability of family life. Method, Method, This study uses 50 respondents citizens of Indonesia who had been a worker abroad namely Malaysia, Hong Kong, Korea and Taiwan. Data collection is done by interview method and secondary data obtained from foreign labor supplier company. Respondents come from 4 districts in eastern Indonesia province of Kediri, Madiun, Ponorogo and Tulungagung. Data were analyzed by quantitative descriptive technique, to find model of fund usage based on activity priority. Result,This research resulted the pattern of foreign usage by Indonesian worker on three activities namely asset purchasing, consumption cost and capital cooperation. There was a slight percentage based on marital status. Workers had already married priority use of funds for asset purchase 26.4%, daily consumption 25.7%, education 13%, venture capital 11.7%, health care 8.8%, and others7.7%. Unmarried workers are the highest priority use of funds for consumption of 19.8%, both asset purchases of 19.5% and third venture capital 13.2%. The findings, this study found the pattern of use of Indonesian labor funds abroad with the main use of funds for consumption and development and sustainability, namely asset purchases, capital cooperation, and education improvement Keywords: man power,funds, capital cooperation, sustainability, district